(C)art Therapy: Sketch Mapping Workshops for Early Teens as a Case Study in Post-representational Cartography - Iverson, Alicia Adelle (My University, 2019)
In this study, I considered the process of mapping as art intervention programming for individuals to uncover the important role that place plays in life’s experiences (affective geographies), specifically the emotions related to the creation of maps towards this purpose. I ask the following three research questions: 1. What impact does the process of mapmaking have on the emotional discovery of the mapmakers, and how can the mapmaking process better serve as a productive, therapeutic experience? 2. What are best practices for using the mapmaking process as an artistic, emotional, place-based research method and pedagogical intervention, in this case with specific regard to adolescents? And, 3. What other benefits does the process of mapmaking have on both map and mapmaker? To answer these questions, I designed a workshop that used the process of cognitive sketch mapping as research method, educational activity, and therapeutic-like experience, enrolling early teenagers from the Bridge Lakepoint Waunona Neighborhood Center (BLW) of Madison, WI. A key insight from this research follows: the process of mapping can do tremendous good as an art-therapy like intervention if the participants (teens) are thoughtfully considered and included at each stage of planning and conducting a mapping workshop, and that cartographic researchers should work in the field getting to know participants in order to best mold a beneficial experience, both emotionally and pedagogically.
Includes Figures, Maps, Satellite images, Photographic images, Appendices and Bibliography.
Keywords: Creative cartographies; Pedagogy; Art intervention; Emotion; Cognitive mapping; Teenagers